Arguably [compact disc, unabridged] : essays - Hitchens, Christopher (Hachette Audio, 2011)
This collection of essays by Christopher Hitchens offers an indispensable key to understanding the passionate and skeptical spirit of one of the most dazzling writers, widely admired for his style, a result of his disciplined and candid thinking. Topics range from why Charles Dickens was among the best of writers and the worst of men to the science fiction of J.G. Ballard; from the legacies of Thomas Jefferson and George Orwell to the persistent agonies of anti-Semitism and jihad.